A Novel Cpw Low Cost Lowpass Filter Integrating Periodic Structures - Fouad Aytouna; Jamal Zbitou; Mohamed Aghoutane; Naima Amar Touhami; Abdelwahed Tribak; Mohamed Latrach (Institute of Advanced Engineering and Science, 2016)
In this work, we propose a novel design of a planar CPW lowpass “LPF” filter based on the use of periodic structures. The periodic cells are formed from a rectangular slot repeated periodically. The originality of this work is to develop a new LPF structure which is simple, low cost for fabrication and easy to associate with others microwave planar circuits. The proposed and validated LPF is a compact planar filter structure. The final circuit is simulated and optimized by using two electromagnetic solvers, ADS (Advanced Design System) and HFSS (High Frequency Structural Simulator). After many series of optimization we have validated the final circuit into simulation by using optimization methods integrated into the both solvers, taking into account a high density of meshing in order to cover the whole circuit. The fabricated LPF circuit shows good agreement between simulation and measurement results in term of matching input impedance and insertion loss with a cutoff frequency of 1.25GHz. The entire area of the proposed LPF is 35x31 mm2.